2021
DOI: 10.1055/s-0040-1721365
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do estado nutricional e correlação com complicações cirúrgicas em pacientes idosos submetidos a tratamento cirúrgico de fratura do fêmur proximal

Abstract: Resumo Objetivo Avaliar e correlacionar o estado nutricional com possíveis complicações no pós-operatório imediato de pacientes submetidos a tratamento cirúrgico de fraturas de fêmur proximal. Métodos Estudo transversal prospectivo analítico e de abordagem quantitativa, tendo como população-alvo pacientes com idade igual ou superior a 60 anos, internados em uma instituição hospitalar no Amazonas, submetidos a tratamento cirúrgico de fraturas de fêmur proximal. Foram avaliadas as complicaçõe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…The MAN scale found similar percentages of malnourished older adults and older adults at risk of malnutrition, which represent, respectively, the first and second most observed findings. Dias et al 13 found that most of their patients were also malnourished or at risk of malnutrition, showing that the nutritional status of older adults is related to the risk of femoral fractures. Regarding the number of comorbidities per patient, most patients had only one comorbidity, followed by those with two comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The MAN scale found similar percentages of malnourished older adults and older adults at risk of malnutrition, which represent, respectively, the first and second most observed findings. Dias et al 13 found that most of their patients were also malnourished or at risk of malnutrition, showing that the nutritional status of older adults is related to the risk of femoral fractures. Regarding the number of comorbidities per patient, most patients had only one comorbidity, followed by those with two comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…A avaliação do estado nutricional nos idosos pode ser realizada utilizando-se vários parâmetros, dentre eles, antropometria e exames laboratoriais. Os parâmetros antropométricos são métodos simples, objetivos, rápidos de serem feitos e de baixo custo 7 . Os exames bioquímicos também são medidas objetivas de avaliação do estado nutricional.…”
unclassified
“…Os exames bioquímicos também são medidas objetivas de avaliação do estado nutricional. Ambos os parâmetros são capazes de mostrar como o paciente está evoluindo nutricionalmente durante o internamento 7 .…”
unclassified